GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 1822 species occurrences available in GBIF matching the query: TaxonKey: Tilapia rendalli (Boulenger, 1897). The dataset includes 1822 records from 39 constituent datasets: 508 records from Fishbase. 912 records from Occurrence records of southern African aquatic biodiversity. 2 records from NCSM Fishes Collection. 13 records from CUMV Fish Collection (Arctos). 2 records from Museu Paraense Emilio Goeldi - ichthyology Collection. 4 records from Museum of Comparative Zoology, Harvard University. 15 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 42 records from Ichthyology Collection - Royal Ontario Museum. 1 records from Colección de Peces Universidad Católica de Oriente. 3 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from CAS Ichthyology (ICH). 6 records from NMNH occurrence DwC-A. 30 records from TNHC Ichthyology Collection. 1 records from Diveboard - Scuba diving citizen science observations. 3 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ichthyology National Collection (MACNIct). 1 records from Northern Territory Museum and Art Gallery provider for OZCAM. 33 records from Natural History Museum (London) Collection Specimens. 13 records from Especies de peces introducidas en aguas continentales de México. Catálogo y manuscrito. 1 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 3 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_ICTIO. 2 records from Fish collection of National Museum of Nature and Science. 1 records from Freshwater Fish Specimens of Lake Biwa Museum. 99 records from rmca-albertine-rift-cichlids. 2 records from CNPE/Coleccion Nacional de Peces. 4 records from Colección Nacional de Peces del IBUNAM. 5 records from UCM Fish Collection (Arctos). 1 records from KUBI Ichthyology Collection. 3 records from Collection Pisces SMF. 3 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 1 records from Field Museum of Natural History (Zoology) Fish Collection. 10 records from Colección Ictiológica de la Universidad de Antioquia. 35 records from NRM-Fishes. 17 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 3 records from Ictiologia Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from AUM Fish Collection. 27 records from USGS Nonindigenous Aquatic Species database. 1 records from UF FLMNH Ichthyology. 1 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 10 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences